Notifiche
Cancella tutti

Integrale

  

1
549

Spiegare e argomentare.

Autore
1 Risposta



1

Prepariamoci alla sostituzione

$ =-\frac{1}{2} \int_0^2 \sqrt{4-x^2} (-2x)  \, dx =$

Poniamo $ t = 4-x^2 \; ⇒ \; dt = -2x \, dx $

inoltre se x = 0 allora t = 4; Se x = 2 allora t = 0

$ =-\frac{1}{2} \int_4^0 \sqrt{t} \, dt =$

$ =\frac{1}{2} \int_0^4 t^{\frac{1}{2}} \, dt =$

$= \left. \frac{1}{2}\frac{2}{3} t^{\frac{3}{2}} \right|_0^4 =$

$= \left. \frac{1}{3} t^{\frac{3}{2}} \right|_0^4 =$

 

$ = \frac{8}{3} $



Risposta
SOS Matematica

4.6
SCARICA